Design and Implementation of Acute Emergency Decision Making Tools to Aid Case Managers: A Focus Group Study - Marquita D. Bradshaw; Nicole B. Washington; Ricky Munoz; Nancy C. Brahm (University of Minnesota Libraries Publishing, 2013)
Objectives: To evaluate and determine if use of specific reference cards for diabetes, stroke, and heat stroke [1] heightened understanding of the signs and symptoms of these conditions and [2] helped case managers (CMs) on the community-based integrated multidisciplinary program of assertive community treatment (IMPACT) team better evaluate patients. Background: Healthcare professionals who service those with a severe mental illness (SMI) diagnosis face many unique challenges. One particular challenge is medical assessment of patients with a SMI diagnosis. Often CMs do not have a background or work experience differentiating medical concerns from psychiatric signs and symptoms. Methods: Reference cards were developed at the request of the IMPACT team. Feedback was elicited through a one-time focus group session conducted by an independent party on the use of the reference cards as an educational tool. Anonymity was maintained. The responses were evaluated for themes. The moderator asked questions regarding the reference cards in each of the following areas: usability when answering questions about hypo- and hyperglycemia, stroke and heat stroke, understanding key points, recommendations for enhancement, and presentation of information. Results: Of the 8 CMs on the IMPACT team, 5 participated. Identified themes were quick reference and easily identifiable information. The use of pictures to illustrate the concepts was helpful. The language was appropriate for the cards and readily understandable. Suggestions for changes to the existing cards included use of a larger font, lighter background color, and moving medication information to the same side of the card. The limited availability of the heat stroke card in the summer was an identified limitation. Conclusions: The use of reference cards as an educational tool for CMs has not been extensively reviewed. Although data are limited from this pilot project, the CMs are enthusiastic about this resource and requested cards on additional topics.   Type: Original Research